Guidelines in Designing the e-Publishing Environment for Handheld Devices : A Study on eInfoC Website - Masniza, Halim (2005)
The dramatic increase in the use and availability of handheld devices such as Personal Digital Assistants (PDAs) in the last few years has resulted in the ability to access information anytime and anywhere. Despite the proliferation of these devices, their usage for accessing the web today is still largely constraint by their small screen display and we are lacking of the standard design guidelines for designing the e-publishing environment on such devices. This paper aims to study the guidelines provided by previous researchers and try to verify the prototype which was built based on the guidelines by interviewing the experts involved in website development, the eInfoC developer, and the user of handheld devices. Finally, the eInfoC website will be designed in a mobile page version.